Speech of the Hon. Sen. J.P.B. Casgrain on navigation of Hudson Bay, Ottawa, Tuesday, February 19, 1907 [electronic resource]. - Casgrain, J. P. B. (Joseph Philippe Baby), 1856-1939. ([Ottawa? : s.n., 1907)
In double columns. Caption title. At head of title: The Senate debates, third session, tenth Parliament. Electronic reproduction. Mode of access: Internet. 44